Improving Students’ Mathematical Problem-Solving Ability Using M-APOS Approach to Derivative Material - R. H. Yanti Silitonga (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2022)
This research is quasi-experimental research that aims to see the improvement of students' mathematical problem-solving abilities on derived material using M-APOS learning. Data analysis using statistical tests on the pretest, post-test, and normalized gain data. Data analysis was carried out with the help of Microsoft Office Excel and SPSS 24 software. The research sample was 66 people who took the differential calculus course. The research instrument is a mathematical problem-solving ability test in the form of a description of four items. This study concludes that there are differences in the increase in mathematical problem-solving abilities of students who receive M-APOS learning with students who receive expository learning. Furthermore, students gave a positive response to M-APOS learning.